The gender gap between water management and water users: evidence from Southwest Bangladesh - Buisson, Marie-Charlotte; Curnow, Jayne; Naz, F. (2017)
Water management in Bangladesh is guided by an intended integrated and inclusive approach enshrined in government legislation since the late 1990s. Based on qualitative and quantitative data collected in the coastal zone, we assess the implementation of these policies with regard to women water uses. First, the analysis of reproductive and productive roles of women establishes that men have a significant role to play in domestic supply, and women use water extensively for small-scale agriculture and aquaculture, the scope of which has been underestimated. However, when considering women's inclusion in community water management and more specifically in Water Management Organizations (WMOs), we demonstrate that women face diverse forms of social barriers resulting in systematic exclusion and self-exclusion from these institutions. Water Management Organizations focus on large-scale productive use of water and are rarely addressing the small scale productive and reproductive uses of water. This creates a gap between water users and water managers, which is exacerbated by class and power relations. The creation of community based water management organisations in the coastal zone of south west Bangladesh has so far not challenged women marginalisation especially in terms of activity limitations and participation restrictions. We conclude by recommending a shift from the inclusiveness policy, which is unable to achieve its goals to a more targeted approach that is relevant in the socio-cultural context of rural Bangladesh.